Development and State of the Art of Entrepreneurship Education: A Bibliometric Review - Saurav Chandra Talukder; Zoltán Lakner; Ágoston Temesi (MDPI AG, 2024)
Entrepreneurship education (EE) plays a vital role in fostering an entrepreneurial culture and promoting the growth of the small- and medium-sized business sector in a nation. Research on EE has advanced extremely rapidly in the last two decades. These changes are evident not only in the quantity of published works but also in the evolving methods of academic communication, the rise of emerging nations as prominent contributors to EE research, and the shifting areas of focus in study themes. This current study aims to provide a comprehensive picture of these processes based on a big-data-centred bibliometric analysis of a corpus of 3787 articles that appeared in the Web of Science literature database. The bibliographic metadata was analysed using Biblioshiny, CitNetExplorer, and VOSviewer. To understand the most significant development trends, researchers employed the triangulation method, which included scientific mapping and epistemological analysis in addition to standard tools of bibliometric analysis. This has led to the identification of some study needs. First, improving EE methods in secondary school curricula; second, EE in adult education and the practicality of the findings for andragogy; third, EE in least developed countries and its unique challenges; fourth, combining EE with internet-based, innovative training and education approaches like gamification and simulations; fifth, EE's role and methodological development in societal economic integration; and sixth, women's unique EE requirements. On top of that, this study provides the basis for policymakers and practitioners to consider incorporating entrepreneurial education programmes, which can help to create a prosperous entrepreneurial ecosystem.